“I HAVE A THOUGHT AND I AM THINKING IT” (CRITICISM OF THE AUDIT APPROACH IN HUMANITIES RESEARCH AND EDUCATION) - Bragina, Natalia; Jermolajeva, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article points out the problem of incompatibility of certain types of humanities research with the standard requirements to scientific paper, which have been developed in recent decades. In humanities studies, the process of reflection and development of a thought is often the main content of scientific work; however in the current standard this aspect is almost ignored. The standard set of requirements imposed upon papers by most scientific journals makes it difficult to obtain the full scientific status for those humanities works that are based on innovative conceptual approach and introduce new perspectives. The aim of this paper is to show the failure of the audit approach to humanities research and substantiate the necessity of extending the current format of a journal article giving it greater freedom and flexibility. In the paper the following methods are used: analysis of relevant literature, method of rationale, historical method, and comparative analysis. The proposed relaxation of the standard requirements to scientific article may stimulate humanities studies that have ground-breaking innovation but do not fit into the standard format. Moreover, it will contribute to the development of conceptual thinking of students of higher school humanities programs, which will create opportunities for more intensive development of the humanities.